PENGARUH KEMISKINAN TERHADAP TINGKAT TINDAK KRIMINALITAS DI KOTA BANDUNG - Dulkiah, Moh. (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
The purpose of this study identifies and explain the influence of destitution with level criminality in Bandung City. This study used the theory of Jeman Sociologist â€œRalf Dahrendorfâ€ that explains about Theory Social Conflict. Social conflict occurs within society because of imbalance in operating of social activities people. This study used a quantitative approach, for the type is case study research. Destitutions level,Â  action criminality level so much, and the other way. Can be concluded the prosperous destitution people, with the result that action criminality level will be the decrease